(untitled) (JIRE: Journal of Islamic Religious Education, 2025)
Inclusive Islamic education plays a crucial role in fostering a supportive and equitable learning environment for children with special needs. Rooted in fundamental Islamic values such as rahmah (compassion), ‘adl (justice), and musawah (equality), this educational approach emphasizes the importance of providing fair and accessible learning opportunities for every student, regardless of their physical, intellectual, or emotional challenges. This article explores the concept and practical application of inclusive education within Islamic-based schools, focusing on strategic approaches that align with Islamic principles. Key strategies discussed include the implementation of differentiated instruction tailored to diverse learning needs, the provision of professional development and specialized training for teachers in handling students with special needs, and the integration of assistive technology to improve access to educational content. Employing a qualitative research design, this study utilizes literature review methods combined with case studies of several inclusive Islamic schools in Indonesia. The findings highlight that the success of inclusive Islamic education is significantly influenced by the presence of strong policy frameworks, active community and parental involvement, and flexible curriculum adaptations that accommodate individual learning profiles. This study concludes that the incorporation of inclusive values within Islamic education not only enhances educational equity but also nurtures a school culture that upholds the dignity and potential of all learners. Inclusive Islamic schools, therefore, can serve as transformative spaces for holistic student development without discrimination.